2017
DOI: 10.1093/carcin/bgx116
|View full text |Cite|
|
Sign up to set email alerts
|

Cellular shear stiffness reflects progression of arsenic-induced transformation during G1

Abstract: Cancer cells consistently exhibit decreased stiffness; however, the onset and progression of this change have not been characterized. To study the development of cell stiffness changes, we evaluated the shear stiffness of populations of cells during transformation to a carcinogenic state. Bronchial epithelial cells were exposed to sodium arsenite to initiate early stages of transformation. Exposed cells were cultured in soft agar to further transformation and select for clonal populations exhibiting anchorage-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…The results indicate that there are statistically significant differences between these two groups, therefore, the disorder strength can be utilized as a marker for a tissue screening. As demonstrated in [ 32 , 33 ], measurement of disorder strength can inform on the mechanical properties of a biological specimen and our results motivate further studies investigating how tissue mechanics vary with disease progression, with disorder strength used as a convenient metric.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…The results indicate that there are statistically significant differences between these two groups, therefore, the disorder strength can be utilized as a marker for a tissue screening. As demonstrated in [ 32 , 33 ], measurement of disorder strength can inform on the mechanical properties of a biological specimen and our results motivate further studies investigating how tissue mechanics vary with disease progression, with disorder strength used as a convenient metric.…”
Section: Resultssupporting
confidence: 54%
“…Images obtained by SLIM has higher contrast than those obtained by other imaging systems, which result in higher phase variance. In addition, tissue biopsy cores generally have a complex structures compared with single cells which were used in the previous works [ 32 , 33 ]. Fig 5 shows the averaged disorder strength across the tissue area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They applied this analysis to colon, skin, and lung cancer cells to demonstrate an inverse relationship between shear stiffness and disorder strength. Building on these results, Muñoz et al 38 used QPI to study the on-set and progression of shear stiffness changes during malignant transformation in bronchial epithelial cells. Our group also showed that the disorder strength measured by spatial light interference microscopy (SLIM), a sensitive white light QPI method, is a quantitative marker of malignancy that can be used to classify benign and malignant breast tissue microarray (TMA) cores.…”
Section: Introductionmentioning
confidence: 99%
“…Building on these results, A. Muoz et al used QPI to study the on-set and progression of shear stiffness changes during malignant transformation in bronchial epithelial cells. 38 Our group also showed that the disorder strength measured by spatial light interference microscopy (SLIM), a sensitive white light QPI method, is a quantitative marker of malignancy that can be used to classify benign and malignant breast tissue microarray (TMA) cores. 8 In this paper, we propose the local spatial autocorrelation length as a new intrinsic marker of nanoscale morphological alteration in fixed tissue biopsies.…”
Section: Introductionmentioning
confidence: 99%